Internet-based conductivity measurement system with self-temperature compensation - Katman, Ratchanoo; Rerkratn, Apinai; Kaewpoonsuk, Anucha (My University, 2019)
An Internet-based conductivity measurement system with self-temperature compensation is presented in the paper. In order to get a simple and portable measurement system, a readout circuit in analog part is designed using only two operational amplifiers (opamps) connected with basic electronic components and energized using single supply voltage. An excitation voltage generated by the AD9833 module is applied to a conductivity sensor. The measured output DC voltages are found to be directly proportional to the conductivity of the solution. The NodeMCU ESP8266 WiFi dev board is used to determine the conductivity and measure the temperature whose effect on the conductivity is compensated. The measured results are sent to display on a smartphone by Blynk app. The conductivity measured by the proposed system is in good agreement with that due to the standard EC meter. A maximum error of measuring the conductivity at different temperatures of solution is 4.79% of full scale.
Keywords: Conductivity measurement; Internet-based measurement system; Single supply; Temperature compensation